Rethinking Terrorism : Terrorism, Violence and the State - Wight, Colin (London Palgrave, 2015)
"This book ... develops a theoretical account of contemporary forms of terrorism and their impact on the international system. Offering a structural explanation for understanding acts of terrorism, it explores the relationship between the state and protest against the state. In placing the state at the centre of the analysis and distinguishing between differing types of political protest and violence, the author gives a deflationary account of terrorism that places severe restrictionson the use of the term"--Back cover.
Include Bibliography and Index
Keywords: Terrorism -- Terrorism--Government policy -- Terrorism--Prevention